KETERLIBATAN AYAH DALAM PENGASUHAN PADA REMAJA AKHIR DI KELUARGA BESAR ANGKATAN DARAT - Vera Angliani Juwita; Prasetyo Adi Nugroho; Afini Freudwi Asri (Fakultas Psikologi Universitas Hang Tuah, 2019)
This study aims to explain the role of father, who works as a soldier, in the care of his children who are in their late adolescence. Based on five components composing father involvement in parenting: positive engangement activities, warmth and responsiveness, control, indirect care, and process responsibility, then measurements were taken on 112 college students. This descriptive quantitative research carried out data processing using descriptive and inferential statistical analysis, especially for non-parametric statistics: Spearman correlation, Mann-Whitney Uand Kruskal-Wallis. The results showed that 50% of respondents rated the involvement of fathers in parenting as being moderate, 38% categorized high and 12% categorized as low. The highest component that composes father involvement is control.